Analysis of water hammer in a penstock in the case of valve closure. Part 1: Without pressure losses - Hocine HAMMOUM; Akli YAHIAOUI; Bachir ACHOUR (Journal of Materials and Engineering Structures, 2016)
We develop, in this paper, a method of calculating the water hammer inspired by the graphic construction of Bergeron, which we qualify as analytical method. In helping us of these graphs, we get the relationships that allow calculating the flow rates and pressures along a penstock. The flow of water is carried out by gravity adduction connecting at upstream a storage tank and at downstream a valve. In this first part, we neglect the pressure losses. The study will focus on water hammer-induced by a slow closing of the valve. A practical example will be presented at the end of this work in order to illustrate the exposed method.